Association of Statin Use With Short- and Long-Term Mortality in Critically Ill Patients With Aortic Stenosis: A Retrospective Cohort Study - Yue Yu; Sanshuai Chang; Ke Shang; Yuemiao Jiao; Yang Li; Liuyang Tian; Guangyuan Song; Chengqian Yin (Journal of Intensive Care Medicine, 2026)
Background Statins have not been shown to modify valvular disease progression in relatively stable aortic stenosis populations, but their prognostic relevance during critical illness remains unclear. Methods We conducted a retrospective cohort study using the MIMIC-IV database. Adult patients with aortic stenosis were included at their first ICU stay if the ICU length of stay was at least 24 h. In-hospital statin prescription exposure was identified from prescription records. The primary outcome was 30-day all-cause mortality after ICU admission, with secondary outcomes at 7, 60, 120, and 365 days. Associations were assessed using hierarchical Cox regression models and propensity score matching (1:1 nearest-neighbor matching; caliper 0.03). Multiple imputation was applied for variables with less than 30% missingness. A 24-h landmark sensitivity analysis was additionally performed for the 30-day primary endpoint. Results A total of 1484 patients were included, of whom 1030 had statin prescription exposure and 454 did not; propensity score matching yielded 706 patients. In the fully adjusted primary model, statin exposure was associated with lower 30-day mortality (hazard ratio [HR] 0.458, 95% CI 0.312-0.674; P < 0.0001). In the matched cohort, statin use remained associated with lower 30-day mortality (HR 0.424, 95% CI 0.269-0.666; P < 0.001). Results The results were materially unchanged in the 24-h landmark sensitivity analysis (HR 0.434, 95% CI 0.288-0.653; P < 0.0001). E-values ranged from 2.80 to 5.91. Conclusions In this retrospective ICU cohort of patients with aortic stenosis, in-hospital statin prescription exposure was associated with lower all-cause mortality across evaluated follow-up time points. Prospective studies that better account for treatment selection and time-varying exposure are warranted.